(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
The states that make up the Sahelian region were born with economic, political-administrative, and social issues, that has made them, today, fertile ground for the emergence and spread of a wide range of non-state groups. In particular, terrorism and organized crime generate unprecedented relationships within power gaps, which contribute to perpetuating spirals of violence, which further destabilize the precarious conditions of the Sahel.